An Experimental Study on the Hardness, Inter Laminar Shear Strength, and Water Absorption Behavior of Habeshian Banana Fiber Reinforced Composites - Shahapurkar K.; Gebremaryam G.; Kanaginahal G.; Ramesh S.; Nik-Ghazali N.-N.; Chenrayan V.; Soudagar M.E.M.; Fouad Y.; Kalam M.A. (Taylor and Francis Ltd., 2025)
The current study examines the effect of NaOH treatment on the hardness, inter-laminar shear strength (ILSS) and water absorption behavior of epoxy composites reinforced with banana pseudostem fibers. Using the hand-lay-up method, six distinct samples are created that are composed of layers of woven and short banana fibers in both a plain and hybrid form. Plain- treated woven composites reveal the highest hardness and ILLS properties followed by the hybrid and short fiber composites. The random orientation of the fiber structure in short fiber composites results in the largest moisture absorption; this behavior is further supported by elucidating the kinetic parameters and diffusion coefficient parameters. SEM analysis confirms the improved surface of the NaOH-treated composite material. ? 2024 The Author(s). Published with license by Taylor & Francis Group, LLC.